New methodology in facial composite construction: from theory to practice. (5th May 2009) - Gibson, Stuart J.; Solomon, Chris J.; Maylin, Matthew I.S.; Clark, Clifford
Existing commercial, computerised techniques for constructing facial composites generated from eyewitness memory are essentially electronic versions of the original, mechanical feature-based systems such as PhotoFIT and Identikit. The effectiveness of this feature-based approach is fundamentally limited by the witness's ability to recall and verbalise accurate descriptions of facial features from memory. Recent advances in facial composite methodology have led to software systems that do not rely on this process but instead exploit a cognitively less demanding process of recognition. We provide a technical overview of the EFIT-V system, currently being used by a number of police services in the UK.